Extracorporeal life support (ECLS) for cardiopulmonary resuscitation (CPR) with pulmonary embolism in surgical patients – a case series. (January 2016) - Swol, J; Buchwald, D; Strauch, J; Schildhauer, TA
Background: Extracorporeal life support (ECLS) devices maintain the circulation and oxygenation of organs during acute right ventricular failure and cardiogenic shock, bypassing the lungs. A pulmonary embolism can cause this life-threatening condition. ECLS is a considerably less invasive treatment than surgical embolectomy. Whether to bridge embolectomy or for a therapeutic purpose, ECLS is used almost exclusively following failure of all other therapeutic options. Methods: From January 1, 2008 to June 30, 2014, five patients in cardiac arrest and with diagnosed pulmonary embolism (PE) were cannulated with the ECLS system. Results: PE was diagnosed using computer tomography scanning or echocardiography. Cardiac arrest was witnessed in the hospital in all cases and CPR (cardiopulmonary resuscitation) was initiated immediately. Cannulation of the femoral vein and femoral artery was always performed under CPR conditions. Right heart failure regressed during the ECLS therapy, usually under a blood flow of 4-5 L/min after 48 hours. Three patients were weaned from ECLS and one patient became an organ donor. Finally, two of the five PE patients treated with ECLS were discharged from inpatient treatment without neurological dysfunction. The duration of ECLS therapy depends on the patient's condition. Irreversible damage to the organs after hypoxemia limits ECLS treatment and leads to futile multiorgan failure. Hemorrhages after thrombolysis and cerebral dysfunction were further complications. Conclusions: Veno-arterial cannulation for ECLS can be feasibly achieved and should be established during active CPR for cardiac arrest. In the case of PE, the immediate diagnosis and rapid implantation of the system are decisive for therapeutic success.